Sleep problems, sleep duration, and use of digital devices among primary school students in Japan - Naoko Sakamoto; Kayoko Kabaya; Meiho Nakayama (BMC, 2022)
Abstract Background There is growing concern that screen time and media use in school-age children can negatively affect children's sleep. These negative effects are explained by three main underlying mechanisms: reduced sleep, time allocated for more media consumption; increased mental, emotional, or psychological stimulation by media content; and the effects of light emitted by digital devices on circadian rhythms and sleep physiology and arousal. In this study, we focused not only on sleep duration, but also on sleep problems. We conducted a large-scale survey to examine the relationship between excessive use of digital devices, Internet addictive behaviour, sleep duration, and sleep problems. Methods We conducted a cross-sectional study of children enrolled in 20 public primary schools in Nagoya City, Japan. Children's parents/guardians completed a questionnaire including the brief sleep questionnaire for Japanese children which is a shortened version of the 'Children's Sleep Habits Questionnaire'. Logistic regression analyses were used to identify associations between sleep problems and grade, sex, weekday sleep time, weekend sleep time, ownership of digital devices, frequent checking of digital devices, use of digital devices for more than 4 hours per day, and Internet addiction. Results In total, 8172 responses were received (91.6% response rate). After excluding incomplete responses, we analysed complete datasets for 6893 children with a mean age of 9.0 years. When adjusted for sex, grade, sleep duration on weekdays, and sleep duration on weekends, failure to control (odds ratio [OR] = 1.48; 95% confidence interval [CI]: 1.29-1.70; p < .001), more use than intended (OR = 1.27; 95% CI: 1.12-1.44; p < .001), and use to escape a dysphoric mood (OR = 1.30; 95% CI: 1.03-1.64; p = .027) were associated with children's sleep problems. A shorter weekday and a longer weekend sleep duration indicated a higher likelihood of sleep problems. Conclusions After adjusting for sleep duration, a relationship was found between the three Internet addictive behaviours and sleep problems, but not ownership of digital devices. Parents and teachers may need to address screen media-related sleep problems in children, as these problems may be influenced by psychological factors.